Influence of acupuncture and acupressure on labor duration: a systematic review - Meneses Neves, Nathália (2024)
Objective: in this regard, the main goal of this systematic review is to identify and compare results that can build different perspectives on the efficacy of acupuncture using work time. Methods: the model followed for the construction of this systematic review was the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The keywords chosen were "Acupuncture" and "Labor Time". Studies originally published were analyzed in English and Portuguese between 1987 and 2020. The selected articles were those including acupuncture and acupressure techniques during labor. Results: 17 articles were in eligibility criteria. In six studies, the use of a standard questionnaire was not described. Sixteen were randomized clinical trials. Fourteen articles had the size of the sample equal to or less than one hundred, and only two exceeded three hundred participants. In most studies (n = 12), the early average acupuncture was between 37 ° and 42 ° week of pregnancy. Ten studies used acupuncture as the main technique. All cited the types of points used, including more present: SP6 and LI4. Conclusion: Acupuncture can be considered an effective technique in reducing the duration of work. However, more high-quality articles are needed to consolidate these positive results.